A novel survey for young substellar objects with the W-band filter III: Searching for very low-mass brown dwarfs in Serpens South and Serpens Core. Issue 3 (19th May 2021) - Dubber, Sophie; Biller, Beth; Allers, Katelyn; Jose, Jessy; Albert, Loïc; Pantoja, Blake; Fontanive, Clémence; Liu, Michael; Zhang, Zhoujian; Chen, Wen-Ping; Lalchand, Bhavana; Damian, Belinda; et al.
ABSTRACT: We present CFHT photometry and IRTF spectroscopy of low-mass candidate members of Serpens South and Serpens Core (∼430 pc, ∼0.5 Myr), identified using a novel combination of photometric filters, known as the W -band method. We report SC182952+011618, SS182959-020335, and SS183032-021028 as young, low-mass Serpens candidate members, with spectral types in the range M7-M8, M5-L0, and M5-M6.5, respectively. Best-fitting effective temperatures and luminosities imply masses of < 0.12M⊙ for all three candidate cluster members. We also present Hubble Space Telescope imaging data (F127M, F139M, and F850LP) for six targets in Serpens South. We report the discovery of the binary system SS183044-020918AB. The binary components are separated by ≈45 AU, with spectral types of M7-M8 and M8-M9, and masses of 0.08–0.1 and 0.05–0.07 M⊙ . We discuss the effects of high dust attenuation on the reliability of our analysis, as well as the presence of reddened background stars in our photometric sample.